Multi-ball rotative nonlinear energy sink for galloping mitigation. (26th May 2022) - Selwanis, Michael M.; Franzini, Guilherme Rosa; Béguin, Cédric; Gosselin, Frédérick P.
Abstract: Galloping is a destructive type of flow-induced vibration (FIV) affecting engineering structures subjected to wind. In this paper, we introduce a simple, low-cost device able to passively absorb the energy of vibrating structures and reduce the galloping amplitudes. This purely nonlinear energy sink (NES) consists of multiple balls rotating freely in a circular track without direct mechanical coupling with the primary system. We assess the benefit of the proposed NES in mitigating the galloping of a square prism through wind tunnel tests and explain the main factors affecting its behaviour. The NES balls rotate due to dynamic interaction with the prism, exhibiting a way of nonlinear energy absorption, which is enhanced by ball collisions. We test different NES configurations varying the number of NES balls to highlight the number of balls' effect on shifting the mass centre and changing the dynamics of the NES. Whereas a single ball NES with a mass 8% that of the prism can increase the critical reduced velocity by 68%, a 2 or 3-ball NES of equivalent mass increases this speed by 87%. Highlights: A multi-ball nonlinear energy sink is effective for galloping mitigation in wind tunnel tests. Balls in a circular racetrack damp galloping through rotation and collisions. Using multiple balls eliminates the strongly modulated response of the prism generated by a single ball NES in the rotational regime. Changing the mass distribution due to balls' motion is a unique advantage of the multi-ball NES. An optimum number of balls achieves the best suppression for galloping without the over-crowdedness of the NES track.